KEBERSIHAN BAGIAN DARI IMAN: PERSEPSI SISWA TENTANG PENGETAHUAN KESEHATAN PHBS DI MADRASAH IBTIDAIYAH - Daryanto, Daryanto; Rina Tri Handayani; Amalia Nurul Fatimah; Muhammad Fauzan Aminudin (Jurnal Tawadhu, 2025)
This qualitative research with a case study design aims to examine the influence of students' knowledge of Clean and Healthy Living Behaviors (PHBS) on their healthy living habits at Madrasah Ibtidaiyah Terpadu Lailatul Qodar. The main focus of this study is to identify how the value of cleanliness in Islamic teachings influences students' behavior, both at school and at home. Additionally, this study analyzes the role of the school environment and parental support in reinforcing healthy lifestyle habits. The research instruments include observation, in-depth interviews with students, teachers, and the school principal. The results indicate that students have good knowledge of PHBS, with high awareness of environmental and personal cleanliness. The values of cleanliness taught in Islam also reinforce their healthy habits. However, the main challenge lies in the limited time of working parents, which reduces interaction and supervision of children's healthy habits at home. This study suggests the importance of collaboration between schools and parents to create an environment that supports healthy living habits consistently.